2018
DOI: 10.48550/arxiv.1810.09536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ordered Neurons: Integrating Tree Structures into Recurrent Neural Networks

Abstract: Natural language is hierarchically structured: smaller units (e.g., phrases) are nested within larger units (e.g., clauses). When a larger constituent ends, all of the smaller constituents that are nested within it must also be closed. While the standard LSTM architecture allows different neurons to track information at different time scales, it does not have an explicit bias towards modeling a hierarchy of constituents. This paper proposes to add such an inductive bias by ordering the neurons; a vector of mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(72 citation statements)
references
References 29 publications
0
72
0
Order By: Relevance
“…In this paper, we introduce the Ordered Memory architecture. The model is conceptually close to previous stack-augmented RNNs, but with two important differences: 1) we replace the pop and push operations with a new writing and erasing mechanism inspired by Ordered Neurons (Shen et al, 2018); 2) we also introduce a new Gated Recursive Cell to compose lower level representations into higher level one. On the logical inference and ListOps tasks, we show that the model learns the proper tree structures required to solve them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations

Ordered Memory

Shen,
Tan,
Hosseini
et al. 2019
Preprint
Self Cite
“…In this paper, we introduce the Ordered Memory architecture. The model is conceptually close to previous stack-augmented RNNs, but with two important differences: 1) we replace the pop and push operations with a new writing and erasing mechanism inspired by Ordered Neurons (Shen et al, 2018); 2) we also introduce a new Gated Recursive Cell to compose lower level representations into higher level one. On the logical inference and ListOps tasks, we show that the model learns the proper tree structures required to solve them.…”
Section: Discussionmentioning
confidence: 99%
“…Ordered Memory is implemented following the principles introduced in Ordered Neurons (Shen et al, 2018). Our model is related to ON-LSTM in several aspects: 1) The memory slots are similar to the chunks in ON-LSTM, when a higher ranking memory slot is forgotten/updated, all lower ranking memory slots should likewise be forgotten/updated; 2) ON-LSTM uses the monotonically non-decreasing master forget gate to preserve long-term information while erasing short term information, the OM model uses the cumulative probability − → π t ; 3) Similarly, the master input gate used by ON-LSTM to control the writing of new information into the memory is replaced with the reversed cumulative probability ← − π t in the OM model.…”
Section: Relations To On-lstm and Shift-reduce Parsermentioning
confidence: 99%
See 2 more Smart Citations

Ordered Memory

Shen,
Tan,
Hosseini
et al. 2019
Preprint
Self Cite
“…Ordered-Neurons LSTMs (ON-LSTMs) Based on the intuition that larger constituents contain information that changes more slowly across the sentence, Shen et al [2018] suggested a variant of LSTMs, called Ordered-Neurons LSTMs, which imposes a hierarchical bias on the cell-updating mechanism. Given the hierarchical nature of our data, we expected ON-LSTMs to perform well on the number-agreements tasks.…”
Section: Rnns With a Structural Biasmentioning
confidence: 99%